High Absorption and Second-Harmonic Generation in Split Ring Resonator Multilayer Nanostructure. (10th July 2014) - Zhou, Renlong; Wu, Mengxiong; Deng, Hui; Liu, Qiong; Xie, Suxia; Wu, Lingxi; Nie, Guozheng; Zhan, Jie
Abstract : Second-harmonic generation in split ring resonator multilayer nanostructure is studied with the finite-difference time-domain (FDTD) method. The fundamental frequency wave and the second-harmonic generation at the resonant absorption wavelength are highly localized in the dielectric layer, and the absorption peak is sensitive to dielectric constant of the dielectric layer. Under the excitation of the plasmon resonances mode, the strong local field induces an expected increase of the second-harmonic generation with conversion efficiencies 10 −6 -10 −7 . The distributions of fundamental frequency electric field and second-harmonic electric field inside the central dielectric layer region are also shown.